Differential expression of MMP-2, MMP-9 and PCNA in endometriosis and endometrial carcinoma - Weigel, Marion T.; Kraemer, Julia; Schem, Christian; Wenners, Antonia; Alkatout, Ibrahim; Jonat, Walter; Maass, Nicolai; Mundhenke, Christoph (European Journal of Obstetrics Gynecology and Reproductive Biology, 2012)
Objectives: Endometriosis is a common gynaecological disease with clinical symptoms such as chronic pain, infertility and intra-abdominal adhesions. Different theories on the pathogenesis of endometriosis and especially its aggressive subtype with infiltrative growth have been discussed. The objective of this study is to evaluate differences in proliferation and invasive properties of invasive colorectal endometriosis, superficial peritoneal endometriosis and endometrial carcinoma (G1 and G2). Study design: Paraffin embedded tissues of peritoneal endometriosis, endometriosis of the intestine and endometrial carcinoma from 97 patients were stained immunohistochemically to assess differences in expression patterns of matrix metalloproteinases (MMP-2, MMP-9) as markers of invasion and the marker of proliferation PCNA. MMP expression was evaluated using the Immuno Reactive Score (IRS) (combining positive cell ratio and staining intensity) and PCNA expression was assessed as the percentage of positively stained cells in representative areas. Results: MMP-2, MMP-9 and PCNA showed differential expression patterns in the different tissues examined. MMP-2 and PCNA expression was stronger in invasive colorectal endometriosis than in superficial peritoneal endometriosis (p = 0.0394). MMP-9, however, was more frequently expressed in peritoneal endometriosis (59.1%) than in colorectal endometriosis (44.4%). This result did not reach statistical significance. When colorectal endometriosis was compared to low grade endometrial carcinoma, proliferation detected by PCNA was significantly higher in endometriosis (p = 0.0008). MMP-2 and MMP-9 showed higher expression in endometrial carcinoma than in endometriosis. Conclusions: There are obvious differences in expression patterns of MMP-2, MMP-9 and PCNA in different stages of endometriosis and in endometrial cancer. These markers can be helpful to evaluate aggressiveness and invasiveness of endometriosis in different localizations. The results obtained could be of relevance for a better understanding of the pathogenesis of endometriosis and the development of an individual therapy concept. © 2011 Elsevier Ireland Ltd. All rights reserved.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Endometrial carcinoma; Endometriosis; MMP-2; MMP-9; PCNA